Comparative analysis of clinical, morphological and prognostic parameters of non-metastatic skin melanoma - K. A. Silakov; O. E. Abramova; E. V. Shako; M. A. Bobrov; P. A. Molotkov; E. R. Chichitko; M. A. Mitrofanov; K. A. Silanteva; P. V. Shegai; G. A. Demyashkin (Исследования и практика в медицине)
Modern understanding of melanoma carcinogenesis and progression highlights the importance of identifying risk factors and prognosis at early stages.Purpose of the study. Analysis of clinical characteristics in patients with skin melanoma.Patients and methods. A retrospective analysis of the medical records of 142 patients with skin melanoma has been carried out. Data on age, gender, tumor localization, disease stage according to the American Joint Committee on Cancer (8th ed., 2017), histological types according to the WHO classification (2022), as well as treatment methods and disease outcomes have been analyzed.Results. Among the studied patients with skin melanoma, women predominated – 78 cases (54.9 %), men – 64 cases (45.1 %). The average age of patients was 63 ± 5.6 years, ranging from 29 to 88 years. Melanoma was most frequently diagnosed at advanced stages: stages IIIA–IIID were detected in 53 patients (37.3 %), stages IIA–IIC – in 40 (28.2 %), and stages 0 and IA–IB – in 16 (11.3 %) and 33 (23.2 %) patients, respectively. The predominant histological types were nodular melanoma (48.6 %) and superficially spreading melanoma (38.7 %). The most common tumor localizations were the skin of the lower extremities (32.3 %) and the back (30.9 %). In 23 patients (16.2 %) with disease progression, metastases were detected in the brain, lymph nodes, liver, lungs, and bones.Conclusions. The carried-out analysis can help clarify the clinical and morphological features of skin melanoma and improve diagnostic and therapeutic approaches.